(untitled) (Global Journal of Management and Business Research, 2015)
The aim of this work is to analyze the effect of financial market anomalies, specifically calendar anomalies, on the behavior of financial investors in terms of decisions and profit. Analyzed in the context of Tunisian financial market into two periods; with two different political regimes, this work examines four calendar effects, which are the weekend effect, the end of the month effect, the January effect and Ramadhan one, contrary to previous studies that have focused on a single effect.